Relationship Between Psychological Responses and the Appraisal of Risk Communication During the Early Phase of the COVID-19 Pandemic: A Two-Wave Study of Community Residents in China - Jin, Zheng; Zhao, Kai-bin; Xia, Yan-yu; Chen, Rui-jun; Yu, Huan; Tamunang Tamutana, Timothy; Yuan, Zheng; Shi, Yi-Ming; Adamseged, Hanna Yeshinegus; Kogay, Marina; Park, Gyun Yeol (Frontiers in Public Health, 2020)
The novel coronavirus (COVID-19) has infected more than 1,000,000 people in at least 120 countries. Data collection in the ascending phase is crucial to deal with a rapidly evolving crisis by understanding the uncertain relation between risk communication and psychological responses. Data were collected from 26th Jan 2020 (at which time 30 Provinces launched the first level response to major public health emergencies in China) until 17th February 2020 (1,775 deaths and 71,429 confirmed cases worldwide) with the mean test-retest interval of 16 days (SD = .82). A cluster sample of 846 adults from four residential communities in high-risk area (Wuhan) and low risk areas (Zhengzhou) were invited to complete a set of Internet-based questionnaires measuring adoption of preventive behaviors, evaluation of risk communication, anxiety level and susceptibility to emotional contagion. Results from cross-lagged models demonstrated reciprocal negative associations between anxiety and risk communication. In addition, the higher evaluation of risk communication in the initial period of outbreak improved adoption of preventive behaviors and mitigated susceptibility to emotional contagion in a later period. Susceptibility to emotional contagion also positively predicted preventive behaviors taken. Furthermore, multiple group structural equation modeling revealed that risk communication is more likely to affect the susceptibility to emotional contagion of people on the frontline of the outbreak compared to people living in low risk areas. This study provided some of the first longitudinal evidence regarding mental health during the COVID-19 outbreak, demonstrated the importance of information campaigns aimed at encouraging appropriate countermeasures against virus outbreaks.